A rare cause of respiratory distress in newborn: posterior mediastinal gastroenteric cyst - Taskin, Erdal; Ozcan, Kenan; Satar, Mehmet; Narli, Nejat; Ozlu, Ferda; Yapicioglu, Hacer (Galenos Yayincilik, 2011)
Presentation of mediastinal enteric cysts are rare during neonatal period. They are mostly asymptomatic. The commonest mode of presentation in neonatal period is repiratory distress. Basically, diagnosis of enteric cyst is histologically, for all that vertebral anomalies associated with posterior mediastinal cyst is property of enteric cyst. 0-24h male patient who diagnosed cystic adenoid malformation of lung on prenatal ultrasonographic examination developed respiratory distress at day 4 of life after birth. Investigations revealed a well defined gastroenteric cyst in the posterior mediastinum with vertebral anomalies. The purpose of this case report is to highlight the clinical diagnosis and management of a neonate with posterior mediastinal enteric cyst. (Turk Arch Ped 2011; 46: 90-2)
Yenido?an döneminde nadir bir solunum sıkıntısı nedeni: Posterior mediyastinal gastroenterik kist
Keywords: Enteric cyst; newborn; respiratory distress